(untitled) (Journal of Engineering and Health Sciences, 2019)
The purpose of this project was to design and fabricate an optimized caliper disc brake for KUIM electric vehicle. There are several properties of the caliper disc brake must be consider to make sure that the product that will produce have a quality from all aspects which are low noise level, life cycle cost, pollution rates, energy consumption, material consumption, provide safety and reliability, and high serviceability. The objective of this work is to design, analyze and investigate the strength and stiffness of the brake caliper during braking operation using ANSYS Workbench 15.0. This analysis is further used to identify the critical locations of low stiffness on the brake caliper and also aimed at evaluating the performance of brake caliper under severe braking conditions. Hence best suitable design is suggested based on the performance and strength criteria.